Manipulating microRNAs for the Treatment of Malignant Pleural Mesothelioma: Past, Present and Future - Reid, Glen; Johnson, Thomas G.; van Zandwijk, Nico (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) are an important class of noncoding RNA that post-transcriptionally regulate the expression of most protein-coding genes. Their aberrant expression in tumours contributes to each of the hallmarks of cancer. In malignant pleural mesothelioma (MPM), in common with other tumour types, changes in miRNA expression are characterised by a global downregulation, although elevated levels of some miRNAs are also found. While an increasing number of miRNAs exhibit altered expression in MPM, relatively few have been functionally characterised. Of a growing number with tumour suppressor activity in vitro, miR-16, miR-193a and miR-215 were also shown to have tumour suppressor activity in vivo. In the case of miR-16, the significant inhibitory effects on tumour growth following targeted delivery of miR-16-based mimics in a xenograft model was the basis for a successful phase I clinical trial. More recently overexpressed miRNAs with oncogenic activity have been described. Many of these changes in miRNA expression are related to the characteristic loss of tumour suppressor pathways in MPM tumours. In this review we will highlight the studies providing evidence for therapeutic effects of modulating microRNA levels in MPM, and discuss these results in the context of emerging approaches to miRNA-based therapy.